(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article presents data from a survey conducted in 26 furniture companies in the country in the period 2023 - 2024. The aim is to diagnose the main limiting factors affecting their functioning; to obtain information about their investment activity for analysis and assessment of the management of the investment process in SMEs by identifying problem areas. The method used is a questionnaire survey among line and functional managers. Conclusions are formulated about the investment needs of the surveyed enterprises.